Group Therapy to Reduce Depression Symptoms in Refugee Immigrants Terapi Kelompok untuk Menurunkan Gejala Depresi pada Imigran Pengungsi - Yudi Kurniawan; Anna Dian Savitri (Universitas Semarang, 2017)
This study aims to measure the decline in depressive symptoms experienced by refugee immigrants through group therapy. Group therapy is used as an intervention to reduce symptoms of depression. The hypothesis was that there was a difference in depressive symptoms score between the experimental and the control group of the immigrant refugee after being given group therapy. This research uses non randomized pretest-posttest control group design. The subjects of the study were 10 immigrants of 30-40-year-old female refugees, divided into experimental and control groups. Non-parametric statistical analysis Mann-Whitney U showed no difference in depressive symptoms score between refugee immigrants experimental group and control group, p = 0,009 (p <0,05). Qualitative analysis shows there is a change of emotional expression on immigrant refugees in the experimental group. The results of this study are important as a study to understand the dynamics of urban clinical psychological problems, particularly those associated with refugee immigrants